Health on thin ice - urban planning for good health in cold climate - Nilsson, Kristina L.; Kostenius, Catrine; Berglund, Lotta; Tossavainen, Mia (Luleå tekniska universitet, Arkitektur och vatten, 2014)
The purpose of the project was to develop a basis for a joint project application regarding urban planning and health promotion in cold climate with the co-partners at OU and if possible with a partner in Northern Norway. The aim was to establish a research platform and cooperation regarding at least one joint research and development application.Two workshops, one at Oulu University and one at Luleå university of technology, have been organized on the theme “urban planning for good health in cold climate”.In Oulu, the research and planning activities regarding the new suburb Hiukkavaara was the major focus on the workshop. In Luleå the resources and challenges with the cold climate and present winter conditions were the topic. Municipalities (Oulu, Pajala and Luleå), the county administrative board the county council of Norrbotten as well as companies were invited to the workshops. Several meetings with the project partners - both video and IRL (in real life) have been organized with researchers at OU and with NTNU, Trondheim. The planned work regarding investigation of cooperation with Tromsö or Finnmark University showed that our research activities and plans did not fit with any research groups at these places. However there was interest for the project both at UiT and at Asplan Viak (a consulting company).A physical research meeting at Ltu in February with researchers from NTNU, OU, Metsähallitus and Ltu resulted in a joint work with a general application that may be adjusted to calls from NordForsk, Horizon 2020, Interreg Nord and Kolarctic ENPI.All planned activities in the project have been performed and the partnership with OU is deepened and a partnership with NTNU is established. The partnership and coming research cooperation will be confirmed with one or several applications for funding projects regarding urban planning for built environment promoting health and wellbeing in cold climate.